2015
DOI: 10.3109/08039488.2015.1080297
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status of psychiatric inpatients at a community teaching hospital in the Midwest

Abstract: Low 25-(OH) D level was found in a high percentage of psychiatric inpatients in Kansas City. Screening for vitamin D deficiency could be a routine work-up for psychiatric inpatients. Vitamin D supplement for African American inpatients with low vitamin D levels could be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Serum 25(OH)D levels in our sample indicate a high prevalence of vitamin D deficiency and insufficiency among hospitalized psychiatric patients. These results are consistent with similar studies conducted by Zeng et al in the US Midwest,41 McCue et al in New York,22 Berk et al in Australia,11 and Humble et al in northern Europe 42. However, in our study, 85% of the sampled patients had lower than normal vitamin D, a much higher level than that identified in similar studies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Serum 25(OH)D levels in our sample indicate a high prevalence of vitamin D deficiency and insufficiency among hospitalized psychiatric patients. These results are consistent with similar studies conducted by Zeng et al in the US Midwest,41 McCue et al in New York,22 Berk et al in Australia,11 and Humble et al in northern Europe 42. However, in our study, 85% of the sampled patients had lower than normal vitamin D, a much higher level than that identified in similar studies.…”
Section: Discussionsupporting
confidence: 94%
“…However, in our study, 85% of the sampled patients had lower than normal vitamin D, a much higher level than that identified in similar studies. A 2016 cross-sectional study in the US determined the prevalence of vitamin D deficiency among psychiatric inpatients and found that 30% of patients had sufficient levels,41 double that of the present study. Per Centers for Disease Control data, ~20%–25% of North American people are considered to be vitamin D insufficient and 7% had hypovitaminosis D 43…”
Section: Discussionsupporting
confidence: 38%
“…In a small scale cohort study in third trimester maternal 25 (OH)D levels were analyzed, the study participants were followed up until the age of 30 and the investigators reported that levels of maternal vitamin D may be associated with an increased risk of schizophrenia (29 vs 46% ) (Eyles et al 2003). Similarly, Zeng and colleagues also evaluated 52 patients and found that 28.8% of the patients in the study had low vitamin D levels and no difference had been seen between major psychiatric diagnoses (Zeng et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are many applications that use sunlight. These studies show the main uses of solar energy and spectral characteristics, including solar power generation [1], daylighting systems [2][3][4][5], mental illness treatment [6], treatment or prevention of human diseases [7][8][9], non-imaging field [10], etc.…”
Section: Introductionmentioning
confidence: 99%